Meta-analysis of the effect of preoperative breast MRI on the surgical management of ductal carcinoma in situ. Issue 8 (28th April 2015) - Fancellu, A; Turner, R M; Dixon, J M; Pinna, A; Cottu, P; Houssami, N
Abstract: Background: MRI has been used increasingly in the diagnosis and management of women with invasive breast cancer. However, its usefulness in the preoperative assessment of ductal carcinoma in situ (DCIS) remains questionable. A meta-analysis was conducted to examine the effects of MRI on surgical treatment of DCIS by analysing studies comparing preoperative MRI with conventional preoperative assessment. Methods: Using random-effects modelling, the proportion of women with various outcomes in the MRI versus no-MRI groups was estimated, and the odds ratio (OR) and adjusted OR (adjusted for study-level median age) for each model were calculated. Results: Nine eligible studies were identified that included 1077 women with DCIS who had preoperative MRI and 2175 who did not. MRI significantly increased the odds of having initial mastectomy (OR 1·72, P = 0·012; adjusted OR 1·76, P = 0·010). There were no significant differences in the proportion of women with positive margins following breast-conserving surgery (BCS) in the MRI and no-MRI groups (OR 0·80, P = 0·059; adjusted OR 1·10, P = 0·716), nor in the necessity of reoperation for positive margins after BCS (OR 1·06, P = 0·759; adjusted OR 1·04, P = 0·844). Overall mastectomy rates did not differ significantly according to whether or not MRI was performed (OR 1·23, P = 0·340; adjusted OR 0·97, P = 0·881). Conclusion: Preoperative MRI in women with DCIS is not associated with improvement in surgical outcomes. Abstract : Does not improve radicality